An example of juridical interaction between the Church and the Crown: The participation of Archbishop Toribio Mogrovejo in the decision-making process of the Hispanic Monarchy (1580-1606) - Tudini, Flavia (2021)
The article aims to demonstrate the importance the role of the archbishop of Lima Toribio Mogrovejo (1580-1606) had for the circulation of information and the decision-making process of the Spanish Monarchy at the end of the 16th century. The article will consider three case studies about the governance of the doctrinas de indios. Through the analysis of the case studies the article demonstrates the influence of the observations and suggestions sent by the archbishop to the king within the decision-making process for the American territories.